2012
DOI: 10.1186/1756-6614-5-11
|View full text |Cite
|
Sign up to set email alerts
|

Case report: When measured free T4 and free T3 may be misleading. Interference with free thyroid hormones measurements on Roche® and Siemens® platforms

Abstract: A 59-year old female patient presented with apathy and 6 kg weight gain. Investigations revealed severe primary hypothyroidism (TSH>100 μIU/ml). L-thyroxine (L-T4) was started and titrated up to 75 μg, once daily, with clinical improvement. Other investigations revealed very high titres of anti-thyroid peroxidase (anti-TPO) and anti-thyroglobulin (anti-Tg) antibodies. After three months, there was a fall in TSH to 12.74 μIU/ml, however, with unexpectedly high free T4 (FT4) - 6.8 ng/ml and free T3 (FT3) - 6.7 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…However, there are other studies which show free T3, freeT4 and T4 levels could be in normal range with increased or decreased serum's TSH level due to the presence of heterophilic antibodies [5,6].…”
Section: Discussionmentioning
confidence: 94%
“…However, there are other studies which show free T3, freeT4 and T4 levels could be in normal range with increased or decreased serum's TSH level due to the presence of heterophilic antibodies [5,6].…”
Section: Discussionmentioning
confidence: 94%
“…The latter adjustment does not correct for specific assay interferences. It has been suggested that two-step methods are less prone to THAAbs interference, because the procedure ensures that there is no contact between serum components and the analog tracer (8, 9). …”
Section: Discussionmentioning
confidence: 99%
“…However, comparison of FT4 results between different methods can be challenging ( 19 , 20 ). One should be aware of these differences between laboratory methods and use the appropriate reference intervals when interpreting results.…”
Section: Discussionmentioning
confidence: 99%